039 Estimating the health and economic burden of investigating tumefactive demyelination compared to conventional multiple sclerosis. (29th July 2019) - Silsby, Matthew; Lopez, Pedro S; Spies, Judy; Reddel, Stephen; Frith, Jane; Barton, Joshua; Beadnall, Heidi; Barnett, Michael; Hardy, Todd
Abstract : Introduction: Tumefactive demyelinating lesions, defined as demyelinating lesions > 2cm in diameter, occur most commonly in association with multiple sclerosis (MS), and can pose a diagnostic challenge. The aim of this study was to estimate the cost and morbidity associated with the diagnostic investigation of patients with tumefactive demyelination (TD) compared to patients with conventional relapsing-remitting MS. Methods: Retrospective review of patients seen between 2013–2018 in clinics at the Brain and Mind Centre, Sydney; a centre with tertiary referral expertise in MS. Records were searched for the terms 'tumefactive' and 'pseudotumour'. All patients diagnosed with TD were included and paired with a patient of similar age diagnosed in the same year with MS according to 2010 McDonald criteria. Results: There were 31 patients with TD and 31 patients with conventional relapsing remitting MS. The estimated cost of investigating TD was more than 7.5 times higher per patient than in MS ($18, 300 AUD vs $2, 418 AUD, p<0.001). Brain biopsy was performed in 6/31 TD patients and 0/31 MS patients and was the cause of more adverse outcomes in the TD versus MS group. More patients in the TD group were admitted to hospital (22/31 vs 10/31) and ICU admissions only occurred in the TD group (10/22 vs 0/10). Conclusion: The cost and adverse outcomes associated with investigating TD are higher than in conventional MS. Improvements in the diagnosis of TD have the potential to improve health and economic outcomes.